Rosenzweig: Temporality of Redemption as Theological-Political Principle - Toscano, Javier (2014)
This essay analyses the temporal structure that Rosenzweig develops mainly in his work The Star of Redemption in order to locate, on one hand, a messianic principle that organizes a specific theologico-political realm, and on the other, to understand the way in which certain terms from the judaic prophetic tradition are refunctionalized to activate in a concrete form a system of thought based on the premise of otherness.